(untitled) (Scottish Historical and Archaeological Internet Reports, 2009)
The surveys have highlighted a number of academic and practical issues crucial to our understanding and management of the monuments. Of first importance is the fact that, with care and even limited resources, such sites can be safely accessed, and can therefore be subject to more detailed research. Both survey and excavation on such sites are practical propositions, and there is therefore little excuse for the neglect of them as a class of monument. Although these monuments are located on the interface between land and sea, and are therefore, as a class, particularly vulnerable to erosion, it cannot be assumed that they are all actively eroding. Nor can assumptions be made about which aspects or areas of even the eroding sites are most at risk. Each monument must be subject to individual assessment and monitoring in order to determine which aspects, if any, of its archaeology are under threat or in the process of destruction.